2011
DOI: 10.2341/10-067-l
|View full text |Cite
|
Sign up to set email alerts
|

The Accuracy of Optical Scanning: Influence of Convergence and Die Preparation

Abstract: SUMMARY The purpose of this study was to determine the reliability of the data acquisition and modeling process of laser and white light scanners by evaluating the reproducibility of digitized simulated crowns with different convergences. A secondary purpose was to analyze the influence of die preparation by testing this hypothesis with a set of dies without ditching compared with a set with well-defined margins. Ditching or trimming the die defines the position of the margin and acts as a guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…The D810, an EAT scanner from 3Shape, is also one of the most popular scanners for the same reasons. These methods of scanning systems have been used to fabricate prostheses in clinics, and earlier studies have shown that their accuracy is acceptable for longterm clinical success [18][19][20] . These scanners were selected for this study as representative systems.…”
Section: Methodsmentioning
confidence: 99%
“…The D810, an EAT scanner from 3Shape, is also one of the most popular scanners for the same reasons. These methods of scanning systems have been used to fabricate prostheses in clinics, and earlier studies have shown that their accuracy is acceptable for longterm clinical success [18][19][20] . These scanners were selected for this study as representative systems.…”
Section: Methodsmentioning
confidence: 99%
“…It can be both time-saving and cost-effective, when compared to conventional casting technology, and many studies have been reported [12,13,14]. Laser sintering is a type of additive manufacturing and a relatively new method compared to both casting and CAD/CAM milling techniques [15,16,17]. This is also called three-dimensional (3-D) printing, or rapid prototyping (RP).…”
Section: Introductionmentioning
confidence: 99%
“…Laser scans at micro-scale can be valuable for production of dental restorations. Impressions taken from dental arch can be scanned entirely or partially with laser or ordinary light at micro-scale to produce die used preparation of dental restoration precisely [24].…”
Section: Reflectionmentioning
confidence: 99%